2020
DOI: 10.1002/agg2.20093
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilizer rate and time effect on dryland no‐till hard red spring wheat production

Abstract: Increasing the efficiency of wheat (Triticum aestivum L.) production is vital for Montana growers' sustainability and competitiveness in the market. Nitrogen fertilizer applications at the right rate and time in the growing season are important for optimizing wheat grain yield and quality. Two dryland field experiments were conducted in North Central Montana in 2014. The effects of N fertilizer rates (28, 84, and 140 kg N ha −1) and application times (seeding, tillering, jointing, and flag leaf emergence) on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
1
12
2
Order By: Relevance
“…Mean grain N uptake values varied substantially by year and location, with the lowest at Soda Springs in 2017 (43.9 kg In this study, grain N uptake was significantly affected by fertilizer N rate at only 4 of 14 site-years (Tables 6-8). This disagrees with findings by Walsh and Walsh (2020a) reporting that grain N uptake was strongly positively correlated with applied N fertilizer rates at both assessed locations. Walsh and Christiaens (2016) reported that N uptake increased with an increase in pre-plant N rates at 7 of the 8 site-years, while topdress N application increased N uptake in 5 of 8 site-years.…”
Section: Grain N Uptake and N Use Efficiencycontrasting
confidence: 99%
See 1 more Smart Citation
“…Mean grain N uptake values varied substantially by year and location, with the lowest at Soda Springs in 2017 (43.9 kg In this study, grain N uptake was significantly affected by fertilizer N rate at only 4 of 14 site-years (Tables 6-8). This disagrees with findings by Walsh and Walsh (2020a) reporting that grain N uptake was strongly positively correlated with applied N fertilizer rates at both assessed locations. Walsh and Christiaens (2016) reported that N uptake increased with an increase in pre-plant N rates at 7 of the 8 site-years, while topdress N application increased N uptake in 5 of 8 site-years.…”
Section: Grain N Uptake and N Use Efficiencycontrasting
confidence: 99%
“…Zhang and Raun (2006) noted that other yield goals in areas like the Midwest were determined by averaging yields from the past 5 yr and adding 20%. Nitrogen‐response trials and historical yields, however, are not always helpful in accurately estimating N (Walsh & Walsh, 2020). According to Raun et al.…”
Section: Introductionmentioning
confidence: 99%
“…When this N was applied at FK 5 , grain yield was likely high because it is the stage at which crop N uptake is high due to accumulation, partitioning, and remobilization of dry matter and N to leaves, stems, grain, and other organs (Zheng et al., 2020). However, when N rate is low, N application at FK 5 is unlikely to result in the highest yield as crops will prioritize the accumulation of grain N over starch (Gaju et al., 2014; Walsh & Walsh, 2020). The interaction between timing and rate of N application has also been found to have a significant effect on winter wheat grain yield (Woodard & Bly, 1998; Zebarth & Sheard, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…A significant spatiotemporal variation in crop response to N is reported for wheat and other crops (Austin et al., 2019; Walsh & Walsh, 2020; Zhang et al., 2018). Wheat is a dominant crop and adoption of conservation tillage has resulted in improvements in soil properties and precipitation use in the US Great Plains region (Peterson et al., 1998).…”
Section: Introductionmentioning
confidence: 99%